The village Indian - Khiḍr, ʻAbbās (Seagull Books, 2013)
Part Odyssey of the Persian Gulf and part "1001 Nights" set in Europe, this debut novel is drawn from the author's experiences as a political prisoner and as a refugee. Our hero, Rasul Hamid describes the eight different ways he fled his home in Iraq and the eight different ways he has failed to find a way home. From Iraq via Northern Africa through Europe and back again, Abbas Khider deftly blends the tragic with the comic, and the grotesque with the ordinary, in order to tell the story of suffering the real and brutal dangers of life as a refugee - and to remember the haunting faces of those who did not survive the journey. This is a stunning piece of storytelling, a novel of unusual scope that brings to life the endless cycle of illegal entry and deportation that defines life for a vulnerable population living on the margins of legitimate society. Translated by Donal McLaughlin, "The Village Indian" provides what every good translation should: a literary looking glass between two cultures, between two places, between East and West.